O conceito de exposição em Walter Benjamin e a fragilidade fértil da filosofia - Silva, Renata Karla Magalhães (2015)
After all, how to understand the concept of presentation (Darstellung) in Walter Benjamin? Why does he use this concept in place of the old acquaintance of philosophy, Vorstellung (representation)? This research aims to investigate the constellation that emerges around these issues. Benjamin argues that the concern about presentation (Darstellung) is inherent in the philosophical text and also is the fragile element of philosophy. This weakness stems from two factors, namely the failure of language, which despite being internally connected to all that exists, is incapable of saying things in its fullness, and the historical and moving character of truth, which moves away every time we try to grasp it. These two factors block philosophy s possibility as a system, but more than that, ask for it to be a constant exercise (Übung) of its form. Instead of denying this weakness, Benjamin proposes to discover the fruitfulness that comes of it: the search for a productive, mimetic, relationship with language. Philosophy thus assumes the form of a continued commitment to the presentation of the truth, while acknowledging the impossibility of fully achieving of this goal. This work aims to show how Benjamin performs this presentation s procedure by his review from the Goethe s novel Elective Affinities, his "pseudotreatise" on the German Baroque and his essay about Surrealism, and how that presentation s exercise can be understood as an experience (Erfahrung) of the object through the practice of philosophical writing